Long term health implications of fitness and physical activity patterns. Issue 12 (December 1991) - Riddoch, C; Savage, J M; Murphy, N; Cran, G W; Boreham, C
Abstract : Northern Ireland has the highest incidence of coronary heart disease (CHD) in the world. The physical fitness, activity patterns, health knowledge, attitudes, and dietary habits of a random, stratified sample of 3211 Northern Irish children, comprising 1540 boys and 1671 girls, age range 11-18 years were examined. At all ages boys were significantly more active than girls. The most important finding was an appreciable decline in physical activity levels after the age of 14 years reaching extremely low levels in older girls. While 75% of exercise taken was not related to school, physical education classes constituted the only exercise taken by one third of pupils. Girls had healthier nutritional habits and were more inclined to employ weight control measures than boys. There was a preponderance of children with a higher body mass index indicating a tendency to obesity in the child population. Over 20% of school leavers of both sexes regularly smoked cigarettes and 20% regularly drank alcohol. The postulated relationship between childhood inactivity, adult sedentary lifestyle, and increased risk of CHD raises serious cause for concern regarding the future cardiovascular health of many children.